Optimization of the Repeating Coil in Three-Coil WPT System - Yan, Boyang; Qi, Xubin; Yang, Yang; Wang, Kun (International Journal of Mechanical and Electrical Engineering, 2024)
This paper examines the optimal conditions for the three-coil Wireless Power Transmission (WPT) system. Initially, an equivalent circuit model was developed Experiments were conducted to explore the impact of the repeating coil parameters and load resistance on the three-coil WPT system. We determined the optimal distance between the transmitting coil and the repeating resonator under various parameters of repeating coil turns, as well as different load resistance, to maximize the system's overall transmission efficiency. It indicates that in the three-coil WPT system, the optimal distance between the transmitting and repeating coils is directly proportional to the load resistance. Moreover, when the turns of the transmitting, repeating, and receiving coils are fixed at seven, the optimal distance changes slightly as the number of turns of the repeating coil increases, but changes significantly when the number of turns decreases. Additionally, when the change in load is constant, an increase in the radius of the repeating coil results in a greater change in the optimal distance. These findings provide important reference information for optimizing the efficiency of triple-coil WPT systems.